The Effect of Board Diversity on Financial Statement Fraud - Salsabila Fitri; Retno Yuni Nur Susilowati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Financial statements have an important role in facilitating all forms of economic activity in the private, public, and non-profit sectors. However, in reality, many companies commit financial statement fraud, causing losses to users. With the increasing attention to financial statement fraud, board diversity has become an important aspect in improving corporate financial reporting monitoring and reducing the possibility of fraud. However, previous studies on the effect of this factor on financial statement fraud still show mixed findings, particularly in the food and beverage manufacturing sub-sector in Indonesia. This study aims to analyze the effect of board diversity on financial statement fraud in food and beverage companies listed on the Indonesia Stock Exchange for the period 2021–2023. This study uses a quantitative approach with secondary data obtained from companies' annual reports and financial statements. Board diversity in this study includes board gender diversity, board age diversity, and board education diversity, all of which are measured using dummy variables. Financial statement fraud is measured using the Beneish m-score. Data analysis is performed using multiple linear regression with the Ordinary Least Squares approach. The results show that board age diversity has a significant negative effect on financial statement fraud. These findings indicate that board diversity is one of the factors that can reduce the likelihood of financial statement fraud.